The level of replacement of employees with PhD degrees in the Republic of Belarus and the prospects of its improvement - Belov Andrei А.; Boreiko, Snezhana A. (Journal of the Belarusian State University. Sociology, 2021)
Based on the available statistical data, an approach to the quantitative assessment of the replacement level of employees with PhD degrees in the Republic of Belarus is proposed in the article. The practical application of this approach made it possible to determine the inefficiency of the postgraduate education system in terms of the annual replenishment of the number of employees with an academic degree. The quantitative parameters of the performance of postgraduate education system which necessary to stabilise the number of employees with PhD degrees in the economy are determined.